Evaluation of drought tolerance of triticale (xTriticosecale Wittm. ex A. Camus) genotypes along with bread wheat and barley genotypes - Seyyed Hamid Reza RAMAZANI; Ali IZANLOO (Acta Agriculturae Slovenica, 2019)
The effects of drought stress on morphological and yield traits of six different genotypes of triticale along with wheat and barley were studied. The experiment was conducted in agricultural college of Sarayan, University of Birjand in 2016-2017 growing season. Experiment was a split-plot experiment based on randomized complete block design with drought stress in main plots and eight mentioned genotypes in subplots in three replications. Results of analysis of variance and means comparison analysis showed significant and negative effect of drought stress on grain yield and biological yield of all investigated genotypes. There was significant difference among investigated genotypes of triticale, wheat, and barley for grain yield under drought stress at 1 % probability level. Pazh genotype of triticale was found as the most drought tolerance genotype, among all investigated genotypes, based on almost all drought tolerance indexes. The highest significant correlation with grain yield was related to biological yield, harvest index, spike/shoot ratio, height and straw yield. GGE biplot analysis of genotypes based on their Yp and Ys showed that Pazh, Jualino, and Sanabad genotypes of triticale had more trends to Ys principal component than ET-89-11 line, wheat, and barley genotypes, therefore show more tolerance to drought stress.